PENGARUH PENYULUHAN DAN DUKUNGAN SARANA PRASARANA TERHADAP KINERJA AGRIBISNIS PADI DI JAWA BARAT - Trisna Subarna (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2007)
The effect of service extension and supporting facilities on the performance of rice agribusiness in West Java Province. The service extension and farming support facilities in agricultural farming play an important role in agribusiness activities. This activity aimed to increase the productivity of integrated rice farming in West Java, reported by these two variables mentioned above have given good contribution to the performance of farmers' group in increasing their productivities. However, both variables have not yet performed optimally in terms of the agribusiness performance. To develop agribusiness in West Java there are three approaches to be chosen includes increasing extension activity, improving supported facilities or both. The aim of this assessment is to investigate the effect of extension service on facilities an infrastructure supported for agricultural farming to the performance of farmers' group in conducting their agribusiness. The assessment was conducted using a survey method in districts of Kuningan, Subang, and Karawang West Java Province from August — October 2006. The parameters that being watched are the performance of agribusiness, extension service activity and facilities support performance, the data were analyzed by path analysis. The results of this study showed:. (1) the activity of farmers guiding through extension service and providing production facilities could improve farmer's productivity, farming efficiency, and their income. (2) the extension service and facilities supports have positive effect on the agribusiness performance. (3) the extension service gave a higher contribution compared to facilities support, this means that farmers guiding plays a better role than the provision of facilities. Key words: agribusiness, exstention service, facilities Penyuluhan dan sarana prasarana usahatani memegang peranan penting dalam pelaksanaan agribisnis padi di Jawa Barat. Pada kegiatan Proyek Peningkatan Produktuvitas Padi Terpadu (P3T) di Jawa Barat dilaporkan kegiatan kedua aspek tersebut dapat meningkatkan produktivitas padi, tetapi belum meningkatkan kinerja kelompok tani dalam agribisnis padi. Untuk pelaksanaan agribisnis di Jawa Barat terdapat tiga pilihan yang perlu ditingkatkan apakah pembinaan petani melalui penyuluhan atau dukungan sarana prasarana kepada petani atau keduanya. Pengkajian ditujukan untuk mengetahui pengaruh penyuluhan dan dukungan sarana dalam pelaksanaan agribisnis. Pengkajian dilaksanakan di kabupaten Kuningan, Subang dan Karawang, pada bulan Agustus sampai Oktober 2006 dengan menggunakan metoda survey. Parameter yang diuji adalah kinerja kelompok tani dalam pelaksanaan agribisnis, aktivitas penyuluhan dan kesesuaian sarana dan prasarana yang diberikan pemerintah bagi petani, analisis data dilakukan dengan analisis jalur (Path Analysis). Hasil pengkajian menunjukkan; (1) Kegiatan penyuluhan dan dukungan sarana prasarana telah meningkatkan produktivitas padi. (2) Penyuluhan dan dukungan sarana prasarana secara bersama-sama berpenganth terhadap kinerja agribisnis. (3) Pengaruh penyuluhan memberikan kontribusi yang lebih besar dibanding dengan dukungan sarana prasarana. Keadaan ini menunjukkan bahwa pembinaan kepada petani lebih berperan dibanding dengan dukungan pemerintah berupa sarana produksi. Kata kunci: agribisnis, penyuluhan, sarana